Scarewaves - Henderson, Trevor (Comics artist) (Henderson, Trevor (Comics artist). Scarewaves (Series), 2023)
"The small town of Beacon Point has always been plagued by eerie local phenomena. It's a town where disappearances are common, strange creatures have been sighted with unnerving frequency, and a ghastly secret lurks in the woods. The adults in town are oblivious to these strange occurrences. Others prefer not to talk or even think about them. But over the course of several terrifying nights, a group of kids will come face to face with the horrors hiding within their sleepy town. Guided by the mysterious radio host Alan Graves, they must follow the clues to a terrifying secret--before it eats them alive."--Page 4 of cover.